Effect of CuO modification on dielectric, ferroelectric and piezoelectric properties of lead-free SrBi4Ti4O15 ceramics - Roshan Jose; Vineetha P; Charan Prasanth S; Ammu Vijay; Venkata Saravanan K (Materials Research Express, 2019)
We report a systematic investigation of the structure, micro-structure, dielectric, ferroelectric and piezoelectric properties of CuO added SrBi _4 Ti _4 O _15 ceramics. All the samples were prepared by solid state reaction technique, where the wt% of CuO in SrBi _4 Ti _4 O _15 was varied as x = 0, 0.05, 0.2, 0.5. The addition of CuO increased the density of SrBi _4 Ti _4 O _15 ceramics which in turn resulted in the improvement of dielectric, ferroelectric as well as piezoelectric properties. However, no change either in the crystal structure or lattice parameter was observed with CuO addition. Further a dense micro-structure with improved electrical properties is expected to be due to liquid phase sintering. Raman spectra and specific heat measurements were also performed for getting further insight into the properties.